PRINSIP AKUNTABILITAS DALAM IMPLEMENTASI PSAK 109 PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN ENREKANG - MOHAMAD IKHMAL AIMAN (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2024)
Accountability is one of the implied elements in the Financial Accounting Standards Statement (PSAK) Number 109 regarding the accounting of zakat, infak, and sedekah.PSAK 109 serves as a guideline for zakat management organizations in the recognition, measurement, disclosure, and presentation of financial statements. By implementing PSAK 109, the accountability of zakat management organizations can be enhanced. This research aims to understand how PSAK 109 is implemented at the National Amil Zakat Agency (BAZNAS) of Enrekang Regency and the factors influencing it, as well as how the principle of accountability is applied in the implementation of PSAK 109 at the National Amil Zakat Agency (BAZNAS) of Enrekang Regency. The type of research used in this study is qualitative descriptive research. The approach employed is a field approach. The data used in this study are primary and secondary data, with data collection techniques carried out using observation, interviews, and documentation techniques. The results of this study indicate that: 1) The National Amil Zakat Agency (BAZNAS) of Enrekang Regency has implemented PSAK 109. This is based on the recognition, presentation, and disclosure, as well as financial reports that are in accordance with what is stipulated by PSAK 109. 2) The main factor underlying the implementation of PSAK 109 at the National Amil Zakat Agency (BAZNAS) of Enrekang Regency is the legal provisions that require zakat management organizations to use PSAK 109. 3) Accountability at the National Amil Zakat Agency (BAZNAS) of Enrekang Regency can be seen from five aspects, namely legal and ethical accountability, managerial accountability, program accountability, policy accountability, and financial accountability. However, there are still obstacles in the implementation of PSAK 109 at BAZNAS Enrekang Regency, namely that the responsible amil do not fully understand PSAK 109. Keywords: PSAK 109, Accountability, Baznas Kab. Enrekang